The Position of Mamak Kepala Waris in High Ancestral Inheritance in Minangkabau Indigenous Community - Ellyne Dwi Poespasari (Jurnal Dinamika Hukum, 2019)
There has been a paradigm shift on the legal stance, role and function of ‘mamak kepala waris’ in ‘harta pusaka tinggi’ –inheritance that has been handed down to generations– in the Minangkabau community. This article examines several legal issues regarding the role of ‘mamak kepala waris’ in ‘harta pusaka tinggi’ in the Minangkabau indigenous community. Firstly, how is the legal position of mamak kepala waris in the management of ‘harta pusaka tinggi’ in Minangkabau. Secondly, how is the current development of the role of ‘mamak kepala waris’ in ‘harta pusaka tinggi’ in the Minangkabau indigenous community. This research is an empirical juridical research with descriptive analysis. The primary data for this study were obtained through observation, interviews with respondents and legal experts, while the secondary data were taken from desk study on legal documents including jurisprudence and legal theories. The results of the study: first, the legal position of ‘mamak kepala waris’ is very important in managing, regulating, supervising and being responsible for the properties that have been inherited through generations (harta pusaka tinggi) for the benefit of nieces. The mamak kepala waris is the holder of the control and maintenance of harta pusaka tinggi of the community. Second: the development of the Minangkabau indigenous people is inseparable from the change in their society, because the Minangkabau people are dynamic and able to keep up with the current development both internally and externally.Keywords: mamak kepala waris, harta pusaka tinggi, matrilineal descent